2021
DOI: 10.1371/journal.pone.0248392
|View full text |Cite
|
Sign up to set email alerts
|

Managing urban solid waste in Ghana: Perspectives and experiences of municipal waste company managers and supervisors in an urban municipality

Abstract: Increased population growth and rapid urbanization have resulted in the generation of large quantities of solid waste across major urban cities in Ghana, outstripping local authorities’ ability to manage and dispose of waste in a sanitary manner. This study explored the perspectives and experiences of municipal waste company managers and supervisors in the Ho municipality of Ghana on solid waste management practices. A qualitative inquiry was conducted by adopting a phenomenological approach, using in-depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…This study found that residents’ inability to sort waste into various compartments during disposal further aggravates the health risk concerns of DWCs. Waste segregation can minimize the potential health risks for DWCs [ 46 , 47 ], since unsorted waste may contain hazardous substances from various sources that can be detrimental to the health of DWCs [ 31 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that residents’ inability to sort waste into various compartments during disposal further aggravates the health risk concerns of DWCs. Waste segregation can minimize the potential health risks for DWCs [ 46 , 47 ], since unsorted waste may contain hazardous substances from various sources that can be detrimental to the health of DWCs [ 31 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the perceptions, beliefs, and behaviors of DWCs can inform policy recommendations on how employers can support and promote healthy work environments among waste workers in Ghana. DWCs are exposed to occupational safety and health hazards in their work due to the huge volumes of solid waste resulting from the ever-growing population [ 31 , 32 ]. The significant increase in the quantity of solid waste has exerted a profound effect on occupational health and safety issues in the solid waste collection and management sector.…”
Section: Introductionmentioning
confidence: 99%
“…One is poverty which induces people not to pay for municipal garbage collection services. This compels them to resort to indiscriminate disposal of garbage in open gutters and vacant plots [38].…”
Section: Study Areamentioning
confidence: 99%
“…Limited road networks in most of the densely populated urban areas does not allow access to the municipal garbage collection vehicles. In such areas, the length of walk to the nearest garbage bins, especially women with young children to cater for, deters them from such exercise [37][38]. Most parts of the city have no integrated drainage networks.…”
Section: Contemporary Environmentalmentioning
confidence: 99%
“…Human behavior in waste management which is part of health behavior is all individual's observable or unobservable activities related to the maintenance and improvement of health (Notoatmodjo 2010). Community behavior in managing inorganic waste is also affected by internal factors, which is awareness within themselves to manage inorganic waste (Chen & Gao 2020;Lissah et al 2021;Pierini et al 2021) and external factors including the availability of facilities and infrastructure as well as support from related parties in managing inorganic waste (Hamudy & Mujaeni 2021).…”
Section: Introductionmentioning
confidence: 99%